Development of Design, Explain, Development, And Evaluation-Project Based Learning (DEDEn-PjBL) Model in Stimulating Children's Creativity - Sadaruddin Sadaruddin; Arifin Ahmad; Baso Jabu; Syamsuardi Syamsuardi; Usman Usman; Hasmawaty Hasmawaty (Lembaga Sembilan Tiga Community, 2023)
This research is research and development which aims to describe the level of need, prototype description, validity, practicality and effectiveness of the Design, Explain, Development, and Evaluation - Project Based Learning (PjBL) model in stimulating early childhood creativity. Data collection techniques through observation, interviews, and questionnaires. Data analysis techniques using descriptive and inferential data analysis. The research procedure begins with the investigation, design, realization, and test-evaluation-revision phases. The description of the needs analysis results shows that teachers need practical and effective learning models to stimulate children's creativity. The prototype description in the form of a model book and teacher's manual has been improved three times based on the input of expert validators and practitioners. It produces the DEDEn-PjBL model that can stimulate children's creativity. The results of the content validity test and the device's validity for all aspects are in the minimal category of